Gamma-irradiation Sterilization in an Inert Environment: A Partial Solution - Berry, Daniel J. (Springer-Verlag, 2011)
BACKGROUND: In the mid to late 1990s, to sterilize UHMWPE bearings, manufacturers changed from gamma-irradiation-in-air (gamma-air) sterilization, which initiated oxidation leading to bearing fatigue, to gamma-irradiation sterilization in an inert environment (gamma-inert). The change to gamma-inert sterilization reportedly prevented shelf oxidation before implantation but not in vivo oxidation. QUESTIONS/PURPOSES: We asked: (1) Has the change to gamma-inert sterilization prevented shelf oxidation that led to early in vivo fatigue damage in gamma-air-sterilized tibial inserts? And (2) has the change to gamma-inert sterilization prevented the occurrence of fatigue secondary to in vivo oxidation? METHODS: We rated 183 retrieved gamma-air- and 175 retrieved gamma-inert-sterilized tibial inserts for clinical fatigue damage and analyzed 132 gamma-air- and 174 gamma-inert-sterilized tibial inserts for oxidation by Fourier transform infrared spectroscopy. RESULTS: Oxidation led to decreased mechanical properties in shelf-aged gamma-air-sterilized tibial inserts. Barrier packaging prevented shelf oxidation in gamma-inert-sterilized tibial inserts. Gamma-air- and gamma-inert-sterilized inserts oxidized in vivo. Fatigue damage (delamination) occurred more frequently in inserts retrieved after longer time in vivo. Longer in vivo time correlated with higher oxidation and more accumulated cycles of use. CONCLUSIONS: Published oxidation projections suggest gamma-inert-sterilized tibial inserts would reach the critical oxidation for the onset of fatigue after 11 to 14 years in vivo. These retrievals appear to follow the projected oxidation trends. Frequency of fatigue damage increased with increasing oxidation. CLINICAL RELEVANCE: Fatigue of tibial inserts becomes more likely, especially in active patients, after more than a decade of good clinical performance.